Banana bunchy top - Niyongere, C.; Omondi, Bonaventure Aman Oduor; Blomme, Guy (CAB International, 2015)
Banana bunchy top disease (BBTD) is caused by Banana bunchy top virus (BBTV), which is transmitted by the aphid vector Pentalonia nigronervosa Coquerel and through infected planting materials. It is one of the most economically important diseases in many banana-producing areas of Africa, Asia and the South Pacific.